"Is it depression, or am I the problem, it's me?" a multimodal analysis on the framing of depression in Psych2Go's Youtube videos - Villafuerte, Michelle Anne Mendoza; Claudio, Ma. Ivy A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study examines YouTube as a new medium for communicating and sharing information on mental health issues. Specifically, it analyzes how depression is framed in Psych2Go's YouTube videos. This study aims to analyze how Psych2Go's YouTube videos utilize audio-visual elements to frame information on depression.

This research employed two theoretical frameworks: Gunther Kress and Theo van Leeuwen's Multimodal Discourse Analysis to explore how meanings of depression are created through the integration of various semiotic resources in Psych2Go's YouTube videos, and Robert Entman and Pan & Kosicki's work on Media Framing to investigate how information in a media text is used a certain way to present frames of depression as manifested in Psych2Go's YouTube videos.

A multimodal analysis, specifically Kress and van Leeuwen's Theory of Composition, is conducted to describe the individual semiotic resources and how they interact with one another in six YouTube videos of P.sych2Go to identify and examine how the patterns of emerging ideas and meanings about depression in the videos are used to frame information about depression.

A thematic analysis revealed four media frames of depression within Psych2Go's YouTube videos: depression affects all types of people, depression is a serious mental illness that comes with complex emotions, depression significantly affects a person's daily life, and depression is treatable.

This study contributed to the way depression is understood within the context Psych2Go's YouTube videos, where depression is described to inform and educate viewers, to understand the emotional challenges and struggles of afflicted individuals, respect different perspectives, and experiences of people with depression, and to promote good habits and self-care activities as a form of treatment.

In an online setting with a large social following these results imply the effective, responsible, and appropriate framing and communication of mental health conditions as it could shape public perception about depression, perpetuate or mitigate misconceptions and stigma about depression, influence beliefs, attitudes, and response towards depression or depressed people, and influence health-seeking behaviors.
Keywords: multimodal discourse analysis, media framing, mental health
communication, depression, Psych2Go, YouTube
Ang pag-aaral na ito ay sumusuri sa YouTube bilang isang bagong midyum pars sa pagbabahagi ng impormasyon tungkol sa mga isyu sa mental health. Inaalam ng pag-aaral na ito kung paano inilalarawan ang depresyon sa mga bidyo ng Psych2Go sa YouTube. Layunin nito na suriin kung paano ginamit ng mga bidyo ng Psych2Go ang mga elemento ng larawan, salita, at tunog upang ilarawan at ilahad ang impormasyon tungkol sa depresyon.

Ang pananaliksik na ito ay gumamit ng dalawang teoretikal na balangkas. Ang mga ito ay ang Multimodal Discourse Analysis nina Gunther Kress at Theo van Leeuwen upang suriin kung paano nilikha ang mga kahulugan tungkol sa depresyon sa parnamagitan ng iba't ibang semiotic resources sa mga bidyo ng Psych2Go sa YouTube, at ang pananaliksik nina Robert Entman and Pan & Kosicki tungkol sa Media Framing upang atamin kung paano nabuo ang impormasyon tungkol sa depresyon sa isang partikular na paraan na ipinakita sa mga bidyo ng Psych2Go sa YouTube.

Ginamit ng pag-aaral na ito ang Theory of Composition ni Kress at van Leeuwen upang ilaravvan ang mga indibidwal na semiotic resources at kung paano sila pagsamahin sa mga bidyo ng Psych2Go sa YouTube. Isinagawa ito upang malaman kung paano ginamit ang mga nabuong ideya at kahulugan tungkol sa depresyon sa paglahad ng impormasyon tungkol sa depresyon sa isang partikular na paraan.

Sa pagsusuri na ito ay nagpakita ng apat na media frame ng depresyon na ginamit sa mga bidyo ng Psych2Go sa YouTube. Ang mga ito ay pinag-usapan ang depresyon sa iba't ibang paraan. Ito ay ang sumusunod: ang depresyon ay nakakaapekto sa lahat ng uri ng tao, ang depresyon ay isang seryosong sakit sa pag-iisip na may kasamang maraming magulong depresyon ay nakakaapckto sit pang-araw-araw na buhay ng isang tao, at ling depresyon ay magagamot.

Ang pag-aaral ay nakapag-ambag sa pagkaintindi sa depresyon sa loob ng konteksto ng mga hidyo ng Psych2Go sa YouTube, kung man inilarawan ang depresyon upang ipalam at turuuan ang mga manonood, upang maunawaan ang mga emosyonal na hamon ng mga taong may depresyon, upang bigyan ng respeto ang iba't ibang pananaw at karanasan ng mga taong may depresyon, at paunlarin ang mga magandang gawi sa pangangalaga sa sarili.

Sa isang online setting na may maraming taong gumagamit, ang mga resulta na ito ay nagpapahiwatig ng isang epektibo, responsable, at angkop na pagpapahayag ng mga kondisyon ng mental health, dahil maaaring itong makapagbago sa pangkalahatang pananaw tungkol sa depresyon, magpatuloy o mabawasan ang mga maling pag-unawa sa depresyon, maimpluwensyahan ang mga paniniwala at tugon sa depresyon o sa mga taong may depresyon, at maimpluwensyahan ang mga health-seeking behavior ng taong may depresyon.

Mga susing salita: multimodal discourse analysis, media framing, komunikasyong mental health, depresyon, Psych2Go, YouTube
Vita.
Undergraduate thesis
Includes bibliographical references (pages 91-101) and appendices (pages 102-185).
Keywords: Social media; Mental health .; YouTube (Electronic resource)